ISOLATION AND IDENTIFICATION OF BACTERIA FROM UDUTH HOSTEL WATER SOURCES (TAPS AND RESERVOIRS) WITH POSSIBLE TREATMENT USING ANTIBIOTICS AND PLANT EXTRACTS (Vernoniaamygdalina & Allium sativum extracts) - Jodi, S. M.; Almajir, M. I. (FUDMA Journal of Sciences, 2022)
Water is essential to life and health; however, more than one billion people worldwide do not have access to safe drinking water (WHO, 2000). Waterborne diseases have been estimated to cause more than two million deaths and four billion cases of diarrhea annually (WHO, 2000). This worked aimed at isolating and identifying bacteria from the tap and reservoir water in UDUTH hostel with possible way of treatment using both conventional antibiotics and plants extracts. Sample were collected from UDUTH hostel, five serial dilutions were done and cultured, the visible colonies were counted and subcultured. Slant bottles were made, the isolates were identified by Gram staining and biochemical tests. After identification the isolates were tested for antibacterial susceptibility test using both conventional antibiotics and plants extracts (Vernoniaamygdalina& Allium sativum extracts). Following Gram staining and biochemical tests, 50% of the isolates were accounted for E.coli, 33% were Staph.aureus, and only 17% of the isolates were Klebsiella spp. The isolates were found to be susceptible to four of the antibiotics used (Ofloxacin, Ciprofloxacin,Gentamacin and Streptomacin) and resistant to two of the antibiotics (Nalixidic acid and Ampicillin). The isolates were also sensitive to two plant extracts used at variable strength.